Comparative analysis of the effectiveness of mechanical treatment of root canals by various Ni-Ti file systems - O. A. Antonova; V. A. Voinova; Yu. A. Mitronin (Эндодонтия Today)
INTRODUCTION. One of the main stages of successful endodontic treatment is high-quality mechanical treatment of root canals. А large number of various rotary Ni-Ti files in the dental market poses a difficult choice for the doctor, especially in the context of import substitution. It is necessary to have knowledge about the effectiveness of different system of instruments in a particular clinical case. AIM. With the help of scanning electronic mycoroscopy and computer microtomography, to analyze the quality of mechanical treatment of the root canal with files of domestic and foreign production.MATERIALS AND METHODS. During the study, single-root and multi-root teeth with different root canal curvature were selected, which were distributed according to the Ni-Ti file system used: group 1 – RM files (RusMed), group 2 – ProTaper Universal (Dentsply Mallifier), group 3 – M-two (VDW).RESULTS. The analysis of scanning electron microscopy of tooth showed that the largest number of open dentine tubules is determined when treating the root canal with instruments of the group 1 (55.4±1.37) and group 3 (60.25±1.59). The centering ability with a curvature of the root canal of 20–25° had no significant differences between the tools used. With a curvature of the root canal of 40–45°, the value of this parameter decreased significantly in all groups of instruments, it was greatest in the groups 1 and 3.CONCLUSION. It was revealed that the best quality of mechanical treatment of the root canal was obtained using RM-files and Mtwo in samples with a channel curvature of up to 25°.